A Framework For Conceptualizing Employee Performance on Hospital - Setiasih, Meli (Faculty of Economics and Business Universitas Jenderal Soedirman, 2023)
High employee performance can be achieved if every element in the organization is well integrated and capable of performing their role. Preliminary survey showed that employee performance had not been optimum. The purpose of this research is to know the influence work life balance, happiness at work, work motivation on employee performance with job satisfaction as intervening variable. The study was conducted at Mother and Children Hospital “Bunda arif” Purwokerto, and mainly utilized quantitative data. The sample for the study were 129 employees. Hypotheses testing device was using Structural Equation Model (SEM). The result showed that work life balance has positive effect on job satisfaction, happiness at work has positive effect on job saticfaction, work motivation has not positive effect on job satisfaction, work life balance has not positive effect on employee performance, happiness at work has positive effect on employee performance, work motivation has positive effect on employee performance, job satisfaction has not positive effect on employee performance, work life balance has not positive effect on employee performance with job satisfaction as intervening variable, happiness at work has not positive effect on employee performance with job satisfaction as intervening variable, and work motivation has not positive effect on employee performance with job satisfaction as intervening variable.